Molecular characterization of pathogenicity locus (PaLoc) and tcdC genetic diversity among tcdA+B+Clostridioides difficile clinical isolates in Tehran, Iran. (December 2020) - Kodori, Mansoor; Ghalavand, Zohreh; Yadegar, Abbas; Eslami, Gita; Azimirad, Masoumeh; Krutova, Marcela; Abadi, Alireza; Zali, Mohammad Reza
Abstract: Clostridioides difficile is the main cause of healthcare-associated diarrhea worldwide. It is proposed that certain C. difficile toxinotypes with distinct pathogenicity locus (PaLoc) variants are associated with disease severity and outcomes. Additionally, few studies have described the common C. difficile toxinotypes, and also little is known about the tcdC variants in Iranian isolates. We characterized the toxinotypes and the tcdC genotypes from a collection of Iranian clinical C. difficile tcdA + B + isolates with known ribotypes (RTs). Fifty C. difficile isolates with known RTs and carrying the tcdA and tcdB toxin genes were analyzed. Toxinotyping was carried out based on a PCR-RFLP analysis of a 19.6 kb region encompassing the PaLoc. Genetic diversity of the tcdC gene was determined by the sequencing of the gene. Of the 50 C. difficile isolates investigated, five distinct toxinotypes were recognized. Toxinotypes 0 (33/50, 66%) and V (11/50, 22%) were the most frequently found. C. difficile isolates of the toxinotype 0 mostly belonged to RT 001 (12/33, 36.4%), whereas toxinotype V consisted of RT 126 (9/11, 81.8%). The tcdC sequencing showed six variants (35/50, 70%); tcdC-sc3 (24%), tcdC-A (22%), tcdC-sc9 (18%), tcdC-B (2%), tcdC-sc14 (2%), and tcdC-sc15 (2%). The remaining isolates were wild-types (15/50, 30%) in the tcdC gene. The present study demonstrates that the majority of clinical tcdA + B + isolates of C. difficile frequently harbor tcdC genetic variants. We also found that the RT 001/toxinotype 0 and the RT 126/toxinotype V are the most common types among Iranian isolates. Further studies are needed to investigate the putative association of various tcdC genotypes with CDI severity and its recurrence. Highlights: Toxinotypes 0 and V are the most frequent type among tcdA + B + C. difficile isolates. RT 001/0 and the RT 126/V are the most common types among Iranian isolates. The majority of tcdA + B + clinical C. difficile isolates harbor tcdC genetic variants.